Wrinkled Skin and Fat Pads in Patients with ALG8‐CDG: Revisiting Skin Manifestations in Congenital Disorders of Glycosylation. Issue 1 (26th November 2013) - Kouwenberg, Dorus; Gardeitchik, Thatjana; Mohamed, Miski; Lefeber, Dirk J.; Morava, Eva
Abstract Glycosylation is the posttranslational coupling of sugar chains to proteins or lipids. Proper glycosylation is essential for normal protein structure, function, and trafficking. Mutations in the glycosylation pathway lead to a phenotypically heterogeneous group of metabolic disorders, the congenital disorders of glycosylation (CDG). Some of these conditions, including PMM2‐CDG, frequently present with recognizable skin abnormalities such as abnormal fat distribution, skin wrinkling, or peau d'orange, whereas others, such as COG7‐CDG and ATP6V0A2‐CDG, have been described in association with cutis laxa: wrinkled, inelastic, and sagging skin. Ichthyosis is also common in several types of CDG. ALG8‐CDG is a severe disorder characterized by dysmorphic features, failure to thrive, protein‐losing enteropathy, neurologic and ophthalmologic problems, and developmental delay. We reviewed the clinical features in all nine previously reported patients diagnosed with ALG8‐CDG with a special focus on their skin signs. Three of the nine patients had abnormal fat distribution and skin wrinkling. As the spectrum of CDG presenting with skin signs expands further, we suggest screening for CDG in all patients presenting with any type of central nervous involvement and wrinkled skin, cutis laxa, severe ichthyosis, or abnormal fat distribution.